A bibliometric analysis and systematic review of drug repurposing against drug-resistant ESKAPE pathogens: a particular focus on Pseudomonas aeruginosa - Guo, Sitong; Li, Lin; Zhang, Qianqian; Liu, Huanxiang; Yao, Xiaojun; Liang, Liang; Chen, Chunxia (Frontiers in Microbiology, 2025)
PurposeDrug-resistant ESKAPE pathogens represent a major global health challenge. This study included a comprehensive bibliometric analysis and systematic review to evaluate drug repurposing efforts against these pathogens, with a particular focus on Pseudomonas aeruginosa.MethodsWe searched the Web of Science Core Collection (2001–April 2025) using the query “ESKAPE AND Drug Resistance AND Drug Repositioning” and performed bibliometric analysis with Bibliometrix (RStudio 4.3.2), VOSviewer 1.6.20, and CiteSpace 6.2R6. In parallel, a systematic review was conducted across PubMed, Embase, Web of Science, and Cochrane Library to identify non-antibiotic agents with reported activity against resistant ESKAPE pathogens.ResultsA total of 443 articles were analyzed bibliometrically, and 141 eligible studies were included in the systematic review, among which 31 focused on drug-resistant P. aeruginosa. The United States, China, and India were the leading contributors, with notable institutional collaborations. Repurposed agents such as niclosamide and mitomycin C exhibited antibacterial activity through mechanisms including membrane permeability disruption, quorum sensing inhibition, and biofilm suppression. Many agents also showed synergistic effects when combined with conventional antibiotics.ConclusionBy integrating bibliometric mapping with systematic evidence synthesis, this study uniquely highlights both research trends and therapeutic potential in drug repurposing for ESKAPE pathogens. While repurposing offers advantages of reduced cost and faster development, translation remains constrained by toxicity, pharmacokinetics, and regulatory hurdles. Limitations include restriction to English-language studies and the use of selected databases. Future efforts should emphasize in vivo validation, clinical trials, and innovative delivery systems to accelerate clinical application.Systematic review registrationhttps://www.crd.york.ac.uk/prospero/, identifier CRD420251053437.